2023
DOI: 10.1039/d2ta09269g
|View full text |Cite
|
Sign up to set email alerts
|

Ni3Fe/Ni3Fe(OOH)x dynamically coupled on wood-derived nitrogen doped carbon as a bifunctional electrocatalyst for rechargeable zinc–air batteries

Abstract: The monolithic air electrode prepared by the integration of wood-derived catalytically activated carbon and alloy exhibits excellent bifunctional activity in zinc–air batteries through optimizing the reaction pathway and accelerating the electrocatalytic kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Rechargeable zinc-air batteries (ZABs) are highly preferred for their high specific energy density, security, and low contamination. However, their commercial application is constrained by the inefficiency of oxygen conversion processes at the air electrode. Currently, Pt-based catalysts are widely applied to oxygen reduction reaction (ORR). The atomic layer deposition (ALD) method was used to put the Pt nanoparticle load on CNTs by Gan et al, which obtained a Pt/CNT catalyst with excellent ORR catalytic activity. Meanwhile, Ru or Ir-based catalysts are applied to oxygen evolution reaction (OER). , A highly universal wet-chemical approach was used to prepare RuO 2 nanowires (NWs) by Yang et al, which showed a lower OER overpotential under acidic and alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable zinc-air batteries (ZABs) are highly preferred for their high specific energy density, security, and low contamination. However, their commercial application is constrained by the inefficiency of oxygen conversion processes at the air electrode. Currently, Pt-based catalysts are widely applied to oxygen reduction reaction (ORR). The atomic layer deposition (ALD) method was used to put the Pt nanoparticle load on CNTs by Gan et al, which obtained a Pt/CNT catalyst with excellent ORR catalytic activity. Meanwhile, Ru or Ir-based catalysts are applied to oxygen evolution reaction (OER). , A highly universal wet-chemical approach was used to prepare RuO 2 nanowires (NWs) by Yang et al, which showed a lower OER overpotential under acidic and alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…7 Consequently, the exploitation of optimal and effective ORR electrocatalysts is a current priority. The Zn-air battery (ZAB), as a highly 4 electron (e − ) pathway ORR-dependent energy storage and conversion device, offers a promising alternative to the traditional lithium-ion battery, 8,9 with a higher energy density (1086 W h kg −1 ), lower cost, and superior safety. 10,11 However, the utilization of strong alkaline electrolytes in ZABs is incompatible with the current wearable electronic devices as it can lead to insoluble carbonates and reduce energy density due to CO 2 poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the exploitation of optimal and effective ORR electrocatalysts is a current priority. The Zn-air battery (ZAB), as a highly 4 electron ( e – ) pathway ORR-dependent energy storage and conversion device, offers a promising alternative to the traditional lithium-ion battery, , with a higher energy density (1086 W h kg –1 ), lower cost, and superior safety. , However, the utilization of strong alkaline electrolytes in ZABs is incompatible with the current wearable electronic devices as it can lead to insoluble carbonates and reduce energy density due to CO 2 poisoning. , To address these issues, recent efforts have explored that near-neutral electrolyte conditions can inhibit zinc dendrites and carbonate situations. , As a result, there is increasing interest in the potential development of neutral electrolyte ZABs, offering a broad prospect for the future of energy storage technology.…”
Section: Introductionmentioning
confidence: 99%
“…The imminent energy crisis and environmental issues are driving the development of highly efficient and environment-friendly clean energy conversion and storage technologies. , Rechargeable Zn–air batteries (ZABs) are attracting widespread interest in grid energy storage, future new energy vehicles, and medical applications due to their cost-effectiveness, a high theoretical energy density of up to 1086 W h kg –1 , excellent security, and eco-friendliness. , In particular, flexible ZABs are expected to serve as a new generation of portable power sources for wearable devices. , Research suggests that the oxygen evolution reaction (OER) is a critical process in ZABs and other new energy technologies but is restricted by sluggish kinetics and high overpotentials. In spite of the good OER catalytic activity achieved by noble-metal-based oxides such as RuO 2 and IrO 2 , their expensive cost and lack of durability continue to hinder the promotion of related energy technologies. , In addition, the electrode materials for current rechargeable ZABs are mostly prepared by the traditional pressing process and the addition of binders, which lead to problems like non-bendability, low energy density, poor cycling stability, etc., limiting their practical application in flexible ZABs . Therefore, it becomes imperative to explore non-precious metal self-supporting catalysts with high activity, strong stability, and superior flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Rechargeable Zn−air batteries (ZABs) are attracting widespread interest in grid energy storage, future new energy vehicles, and medical applications due to their costeffectiveness, a high theoretical energy density of up to 1086 W h kg −1 , excellent security, and eco-friendliness. 3,4 In particular, flexible ZABs are expected to serve as a new generation of portable power sources for wearable devices. 5,6 Research suggests that the oxygen evolution reaction (OER) is a critical process in ZABs and other new energy technologies but is restricted by sluggish kinetics and high overpotentials.…”
Section: Introductionmentioning
confidence: 99%